Pelatihan Si Cerdik Akuntansi Dasar Hidup Hemat dan Kreatif di Masa Pandemik - Tri Utami; Wiwit Irawati; Zulfa Rosharlianti; Dea Annisa; Dila Angraini (Universitas Pamulang, 2021)
Community Service (PKM) in collaboration with the UFO Reading Terrace, Kedaung. The purpose of this PKM is to introduce and provide training to UFO Reading Park children about the basics of frugal and creative living during the Pandemic. There are 20-30 children from the UFO Reading Gardens who are involved in this PKM with teaching time on October 30, 2021. The methods used in this PKM are counselling or lectures, tutorials, discussions, and mentoring. The results of PKM from 20-30 children at the UFO Reading Park show that most of them already understand the importance of living frugally during this pandemic but have not been able to record it neatly in their wallets. It is hoped that this PKM will be useful for various parties including the children of the UFO Reading Park itself, the surrounding community and for academics.